Brain Stimulation and Constraint Induced Movement Therapy in Children With Unilateral Cerebral Palsy: A Randomized Controlled Trial. (May 2023) - Gupta, Juhi; Gulati, Sheffali; Singh, Upinder Pal; Kumar, Atin; Jauhari, Prashant; Chakrabarty, Biswaroop; Pandey, Ravindra Mohan; Bhatia, Renu; Jain, Suman; Srivastava, Achal
Background: There is a crucial need to devise optimum rehabilitation programs for children with cerebral palsy (CP). Objective: This study aimed to assess the feasibility, safety, and efficacy of combining 6-Hz primed, low-frequency, repetitive transcranial magnetic stimulation (rTMS) with modified constraint-induced movement therapy (mCIMT) in improving upper limb function in children with unilateral CP. Methods: Children aged 5 to 18 years with unilateral CP were randomized (23 in each arm) to receive 10 sessions of mCIMT with real rTMS (intervention arm) or mCIMT with sham rTMS (control arm), on alternate weekdays over 4 weeks. The primary outcome was the difference in mean change in Quality of Upper Extremity Skills Test (QUEST) scores. Secondary outcomes were changes in QUEST domain scores, speed and strength measures, CP quality of life (CP-QOL) scale scores, and safety of rTMS. Results: All 46 children completed the trial except one. At 4 weeks, the mean change in total QUEST scores was significantly higher in the intervention arm as compared to the control arm (11.66 ± 6.97 vs 6.56 ± 4.3, d  = 5.1, 95% CI 1.7-8.5, P  = .004). Change in "weight bearing" and "protective extension" domain score was significantly higher for children in the intervention arm. These improvements were sustained at 12 weeks ( P  = .028). CP-QOL scores improved at 12 weeks. No serious adverse events were seen. Conclusion: A 6-Hz primed rTMS combined with mCIMT is safe, feasible, and superior to mCIMT alone in improving the upper limb function of children with unilateral CP. Trial Registration: ClinicalTrials.gov Identifier: NCT03792789.